Lâminas de irrigação, polímero hidrorretentor e volume de cova no cultivo do maracujazeiro-amarelo - Nascimento, Ana Paula Pereira do (2021)
The yellow passion fruit is a fruit tree of economic importance in Brazil, with the Northeast region responsible for 64.5% of the national production. However, the biggest obstacle to the development of culture in the semi-arid region of the Northeast is still due to the limitation of water resources in quantity and quality required by the culture. In this sense, the objective of the research was to evaluate the effect of the water-retaining polymer in two types of pits subjected to irrigation depths in the yellow passion fruit (Passiflora edulis Sims) cv. Gigante Amarelo – BRS GA1. The work was conducted in the municipality of Remígio, Paraiba Brazil. The soil of the experimental area was classified as Regolithic Neosol, dystrophic, non-saline. The experiment was carried out in a randomized block design in split plots, with eight treatments and three replications totaling 72 plants using a 2 × 2 × 2 factorial scheme, relative at irrigation depths of 70% and 100% of the evapotranspiration requirement of the crop (ETc), holes with a volume of 64 and 128 dm3, in the soil without (0.0) and with 1.5 g dm-3 of waterretaining polymer. The plots corresponded to the irrigation depths and the subplots to the combinations between the volume of the holes and the water-retaining polymer. The results regarding fertility and plant growth in the field are found in chapter I (Irrigation blades, waterretaining polymer and hole volume on soil fertility and yellow passion fruit growth, pg. 14 to 73 ); the aspects of plant physiology are shown in chapter II entitled (Irrigation blades, waterretaining polymer and pit volume in chlorophyll, gas exchange and yellow passion fruit productivity, pg. 74 to 99).